Floored when seven lives collide a novel - Barnard, Sara; Bourne, Holly; Byrne, Tanya; Pratt, Non; Salisbury, Melinda; Williamson, Lisa; Wood, Eleanor (Macmillan Children's Books, 2018)
When they got in the lift, they were strangers Sasha, Hugo, Velvet, Dawson, Kaitlyn and Joe, who shouldn't be here at all, but who wants to be here the most. And one more person, who will bring them together again on the same day every year.